PENGARUH SUHU DAN LAMA CURING TERHADAP KANDUNGAN SENYAWA BIOAKTIF EKSTRAK ETANOL BUNGA KECOMBRANG (Nicolaia speciosa Horan) - Hasbi Muhammad, Panji; Wrasiati, Ni Luh Putu; Anggreni, A.A.M. Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember, 2015)
This research were aimed to 1) investigate the effect of curing temperature and curingtime  to bioactive compounds  of  kecombrang  flower  extract  2) to determine an appropriatecuring temperature and  curing  time  that was able to  produce  the  higest  bioactive compoundsof kecombrang flower extract. Solvent used for the extraction was ethanol.This experiment  used  randomized block design with  2 factors. The first factor was the curing temperature consists of 2 levels namely 30 ±2 oC and 40 ±2 oC. The second factor was curing time  consists of 4 levels namely  3 hours,  6 hours,  9 hours  and 12 hours. The objective data analyzed using ANOVA followed by Duncan test and  subjective data analyzed with the Friedman test. This research conducted twice to obtain 16 units experiment. The results showed that  curing temperature and  curing  time  had high  significantly  effect on rendement, tannin, anthocyanin of kecombrang flower extract while the interaction was not significant. Curing temperature, curing time and its interaction had high significantly effect on pH.  The  curing  treatment  at  40 ±2 oC  for 3 hours had the highest  characteristic extract of kecombrang flower at  3.51%  rendement,  4.68  pH,  0.81%  tannin,  2.06  mg/L  anthocyanin,  5.1 score of hedonic (between rather like to like) and 7.10 flavor strength.
Keywords: 76